Plastid phylogenomic study of grape species and its implications for evolutionary study and conservation of Vitis - Mu, Xian-Yun; Shen, Xue-Li; Wu, Yuan-Mi; Zhu, Yi-Xuan; Dong, Shu-Bin; Xia, Xiao-Fei; Lin, Qin-Wen; Fan, Pei-Ge; Liu, Yu-Lin; Zhang, Zhi-Xiang (Phytotaxa, 2018)
Because of rapid diversification and frequent interspecific gene flow within the genus and inappropriate molecular markers used for phylogenetic studies, phylogeny and evolution of the economically significant crop genus Vitis are poorly resolved and understood, and species delimitation of Vitis remain disputable. In order to better understand of relationships within Vitis, phylogenomic analysis of chloroplast genomes were performed based on extensive sampling scheme. Well resolved phylogenetic tree and clear divergence pattern of Vitis were obtained in the present study. The results shows that subg. Vitis was constituted by three strongly supported monophyletic clades whose species are distributed in North America, Europe and Asia, respectively. Nine molecular markers are provided as potential markers for DNA barcoding and phylogenetic study of Vitis. Furthermore, taxonomic position of the critically endangered species endemic to Northern China, V. baihuashanensis, is investigated and suggested to be a separate species based on phylogenomic analysis and morphological comparisons, and effective conservation actions is badly needed. Molecular resources reported in this study could also be used for genetic engineering studies of Vitis, and will potentially promote genomic exploration of crop wild relatives and conservation of the germplasm.